STRATEGI PEMBANGUNAN CITRA MELALUI KONTEN PRODUK LOKAL TIKTOK PADA DCT AGENCY - Akbar Nurizki (Indonesian Journal of Digital Public Relations (IJDPR), 2023)
DCT Agency is an agency with services that accommodate brand image creation for local products through TikTok by involving content creators. The demand for brand image creation for local products and the role of TikTok content creators create an urgency for research on the topic. This research uses qualitative methods through interview and observation on DCT Agency. Data on this research is based on corporate identity, corporate communication, corporate image & reputation, and competitive advantage as analysis units and analysed through data reduction, data display, and verification. The result for this research explains DCT Agency's branding strategy through local product content on TikTok by considering the right targets, content that fits the brand identity, and relationships with the audience. Keywords: branding, DCT Agency, local product content, TikTok